Observations of Diurnal to Weekly Variations of Monoterpene-Dominated Fluxes of Volatile Organic Compounds from Mediterranean Forests: Implications for Regional Modeling - Fares, Silvano; Schnitzhofer, Ralf; Jiang, Xiaoyan; Guenther, Alex; Hansel, Armin; Loreto, Francesco (ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2013)
The Estate of Castelporziano (Rome, Italy) hosts many ecosystems representative of Mediterranean vegetation, especially holm oak and pine forests and dune vegetation. In this work, basal emission factors (BEFs) of biogenic volatile organic compounds (BVOCs) obtained by Eddy Covariance in a field campaign using a proton transfer reaction-time-of-flight-mass spectrometer (PTR-TOF-MS) were compared to BEFs reported in previous studies that could not measure fluxes in real-time. Globally, broadleaf forests are dominated by isoprene emissions, but these Mediterranean ecosystems are dominated by strong monoterpene emitters, as shown by the new BEFs. The original and new BEFs were used to parametrize the model of emissions of gases and aerosols from nature (MEGAN v2.1), and model outputs were compared with measured fluxes. Results showed good agreement between modeled and measured fluxes when a model was used to predict radiative transfer and energy balance across the canopy. We then evaluated whether changes in BVOC emissions can affect the chemistry of the atmosphere and climate at a regional level. MEGAN was run together with the land surface model (community land model, CLM v4.0) of the community earth system model (CESM v1.0). Results highlighted that tropospheric ozone concentration and air temperature predicted from the model are sensitive to the magnitude of BVOC emissions, thus demonstrating the importance of adopting the proper BEF values for model parametrization.
The following values have no corresponding Zotero field: pub-location: 1155 16TH ST, NW, WASHINGTON, DC 20036 USA publisher: AMER CHEMICAL SOC
Keywords: Emissions; GLOBAL-MODEL; Ozone; PROTON-TRANSFER REACTION; PTR-TOF; QUERCUS-ILEX; REACTION MASS-SPECTROMETRY

STOMATAL DENSITY VARIATION IN BEECH AND HOLM OAK LEAVES COLLECTED OVER THE LAST 200 YEARS - Paoletti, E; GELLINI, R (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 1993)
In leaf samples of Fagus sylvatica L. and Quercus ilex L. collected over the last 200 years a reduction has been observed in the stomatal density of 43% and 28% respectively. The ecological implications, particularly concerning atmospheric CO2 increase and drought tolerance, are discussed.
Keywords: ATMOSPHERIC CO2 INCREASE; FAGUS-SYLVATICA; QUERCUS-ILEX; stomatal density

COMPARISON OF THE HYDROLOGICAL CHARACTERISTICS OF 3 SMALL EXPERIMENTAL HOLM OAK FORESTED CATCHMENTS IN NE SPAIN IN RELATION TO LARGER AREAS - Piñol, J; Avila, a; Escarre, A; LLEDO, M J; Rodà, F (VEGETATIO, 1992)
Precipitation and streamflow have been measured in three small (0.04-0.52 km2) experimental catchments covered by dense holm oak (Quercus ilex L.) forests. Two of them are in the Prades mountains and one in the Montseny mountains (NE Spain). Here we test the hydrological representativeness of these catchments against the streamflow record at two nearby larger (34-60 km2) catchments, one from each massif. Comparisons of (i) annual streamflow, (ii) seasonal distribution of streamflow, and (iii) flow duration curves were made. At Prades, for the period of common record, mean annual precipitation was about 580 mm, and mean annual streamflow 44-81 mm at the two experimental catchments and 102 mm at the larger one. Most streamflow occurred during winter and spring in the three catchments. At Montseny, rainfall was higher, and mean annual streamflow was 495 mm in the experimental catchment, and 760 mm in the larger catchment, though these data were obtained in different periods in each catchment. Streamflow was roughly equal in autumn, winter and spring. At both sites flow duration curves were fairly similar in the small experimental catchments and the larger catchments. The higher streamflow at Montseny is reflected in its flow duration curves being well above those at Prades. The experimental catchments at Prades are thus fairly representative of the investigated hydrological characteristics. At Montseny, hydrological differences between the experimental catchment and the larger catchment are probably due to the higher mean altitude of the latter and to the non-overlapping periods of their streamflow records.
Keywords: EXPERIMENTAL CATCHMENT; montseny; prades; QUERCUS-ILEX; STREAMFLOW; Water budget

DESICCATION TOLERANCE AND OSMOTIC PARAMETERS IN DETACHED LEAVES OF QUERCUS-ILEX L - KYRIAKOPOULOS, E; RICHTER, H (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 1991)
Batches of detached Quercus ilex leaves from a natural site were desiccated to different relative water contents. The percentage of necrotic leaf area was evaluated after resaturation, and necrosis of 1-2% defined as ``incipient injury{''}. The relative water content at incipient injury was higher in the dry summer than in the humid winter. Osmotic potentials of young leaves decline rapidly during leaf maturation; the values are not closely coupled to desiccation tolerance. The results are discussed with reference to the evolutionary origins of Quercus ilex, an Arcto-Tertiary element of the Mediterranean flora.
Keywords: DESICCATION TOLERANCE; OSMOTIC PARAMETERS; QUERCUS-ILEX